2010
DOI: 10.1021/jp102217u
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Solvatochromic Probe Behavior within Ionic Liquids and (Ionic Liquid + Water) Mixtures

Abstract: Spectroscopic responses of absorbance probes, betaine dye 33, N,N-diethyl-4-nitroaniline, and 4-nitroaniline, and fluorescence dipolarity probes, pyrene (Py) and pyrene-1-carboxaldehyde (PyCHO) within ionic liquids (ILs) 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF6]) and 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim][BF4]), and aqueous mixtures of [bmim][BF4] are used to assess the changes in important physicochemical properties with temperature in the range 10-90 degrees C. ETN obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 123 publications
6
68
2
Order By: Relevance
“…The self-assembly behaviour of CetPySal in aqueous medium was performed using multi technique approach. [32][33][34][35][36]48] Surface active and micellization parameters derived from the surface tension and conductivity measurements are reported in Table 1 and are compared with precursor surfactant CPCl. [48] Plots of surface tension and specific conductivity (k) versus [CetPySal] are shown in Figure 1.…”
Section: Self-assembly Of Cetpysal In Aqueous Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…The self-assembly behaviour of CetPySal in aqueous medium was performed using multi technique approach. [32][33][34][35][36]48] Surface active and micellization parameters derived from the surface tension and conductivity measurements are reported in Table 1 and are compared with precursor surfactant CPCl. [48] Plots of surface tension and specific conductivity (k) versus [CetPySal] are shown in Figure 1.…”
Section: Self-assembly Of Cetpysal In Aqueous Mediummentioning
confidence: 99%
“…Our group is engaged in designing various amphiphilic molecules for their tailor made interfacial and micellar properties, ionic liquid based surfactants (ILBS) with better surface active and micellar properties than the traditional surfactants are one of them. [30][31][32][33][34][35][36] Herein we had designed salicylate based IL (Figure 1a), cetylpyridinium salicylate (CetPySal) that show better surface active and micellar properties than its precursor surfactant cetylpyridinium chloride (CPCl) and exhibited temperature responsive gel-to-gel phase transition. The cationic precursors of the CetPySal, CPCl is known for the antiseptic and antibacterial activity as well as have applications in various fields including mouthwashes, toothpastes and in various pharmaceutical formulations among others.…”
Section: Introductionmentioning
confidence: 99%
“…The Kamlet-Taft parameters (a, b, and p à ) are temperature-dependent solvent polarity scales (Lee and Prausnitz, 2010;Trivedi et al, 2010) and similar as described for Abraham equation. For RTILs, Kamlet-Taft parameters can be easily measured by uv/vis spectroscopy in the presence of solvatochromic dyes; the most common being Reichardt's dye (RD), N,N-diethyl-4-nitroaniline (DENA), and 4-nitroaniline (4NA).…”
Section: Solvation Properties Of Rtilsmentioning
confidence: 99%
“…Comprehensive studies on the interactions between mixtures of gemini and conventional single chain surfactants of different charge classes to form mixed micellar aggregates have been reported [31][32][33][34]. In recent decades, studies on the interactions between single chain surfactants and IL have been reported and the results obtained are discussed at length [35][36][37][38][39][40][41][42][43][44][45][46]. Pandey et al [35][36][37][38] reported the dual behavior of IL in aqueous solutions of single chain surfactants.…”
Section: Introductionmentioning
confidence: 99%